Pengaruh Harga, Brand Trust, dan Kualitas Pelayanan terhadap Keputusan Pembelian Menggunakan Jasa Pengiriman Shopee Xpress (Studi pada Masyarakat Kota Malang) - Dhafa, Genta Mulya; Asiyah, Siti; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the influence of price, brand trust, and service quality on purchasing decisions using Shopee Xpress delivery services. The research method used was quantitative with a descriptive approach. Data were collected through questionnaires from 85 respondents from Malang City. Analysis was conducted using multiple linear regression. The results showed that price, brand trust, and service quality simultaneously had a significant influence on purchasing decisions. Partially, each variable also had a positive and significant influence on purchasing decisions. These findings suggest that companies need to maintain service quality, strengthen brand trust, and maintain a competitive pricing strategy. Keywords: Price, Brand Trust, Service Quality, Purchasing Decisions, Shopee Xpress